ADASP recommendations for processing and reporting of lymph node specimens submitted for evaluation of metastatic disease - Lawrence, W.; Pathology, Association (Virchows Archiv : an international journal of pathology, 2001)
It is well known that different pathologists in different laboratories follow different protocols for the processing and examination of these specimens. There is also extensive literature (some of which is summarized in the references appended to the present report) on the likelihood of identifying metastases of varying sizes with different methods of preparation, as well as on the clinical significance of this identification, which varies not only from site to site but also from report to report on the same site. The Association of Directors of Anatomic and Surgical Pathology (ADASP) has reviewed this literature as well as the personal experience of its own members to present a set of recommendations for lymph node biopsies, lymph node dissections, sentinel node biopsies, lymph node fine needle aspiration (FNA) and core needle biopsies. It should be noted that these recommendations are intended specifically for lymph nodes being studied for metastatic neoplasms, and are not intended to apply to lymph nodes being evaluated for lymphoma, infections, and other disease processes. They are, however, formulated generically enough to apply regardless of whether the primary tumor is a carcinoma of the breast, carcinoma of the prostate, melanoma, or any other malignant, potentially metastasizing tumor. The Association has published numerous documents with recommendations for reporting surgical pathology specimens involving particular organ sites (for example, breast, pancreas, thyroid, etc.) However, the Association has not yet considered the generic question of dealing with lymph node specimens in which the intent is to search for and document the presence of metastatic disease. We are also unaware of guidelines for pathologists published by any other organization on this subject.